Combining Energy Management Indicators and Life Cycle Assessment Indicators to Promote Sustainability in a Paper Production Plant (2020)
This paper presents the application of an energy characterization method based on the ISO 50001 standard in a dry paper production plant. This plant operates using electricity, gas, and coal as energy sources. The last two energy sources are used to produce the steam and hot air used in the paper drying process. Through energy characterization, indicators such as energy baseline and consumption indicators were calculated for the plant, with which improvement opportunities were identified. These improvement opportunities were used as case studies for each energy source used and were based on the actual state of the plant. 2011 Midpoint+ ILCD method data was selected from the Ecoinvent database, using OpenLCA 1.7.0 for the energy assessment. The impact categories analyzed in this study were ecotoxicity, eutrophication of rivers and seas, climate change, and human toxicity. As a result of this work, it was found that energy-saving was possible by adjusting the production rate to a load factor of 77%, which implies a gas consumption of 1.6 kWh/kg and a value in the climate change category of 88.5 kg of CO2 equivalent. In addition, some technological improvement opportunities were economical and environmentally evaluated as a result of the sustainable improvement strategy implemented with energy management and life cycle assessment. The study of these technological opportunities showed that in order to achieve a sustainable industrial process, it is important to take into account energy, economic, and environmental criteria in the continuous improvement of the paper production process. In addition, it is of vital importance to analyze alternatives for technological change, which have a greater impact than operational alternatives according to energy, environmental and economic criteria.